Invasive pulmonary aspergillosis in a captive bird Cyanocompsa brissonii (Cardinalidae) in Mendoza, Argentina - Palma Leotta, M.; Pelegrina, M.; Cáceres, A. (Revista Veterinaria, 2016)
Palma Leotta, M.; Pelegrina, M.; Cáceres, A.: Invasive pulmonary aspergillosis in a captive bird Cyanocompsa brissonii (Cardinalidae) in Mendoza, Argentina. Rev. vet. 26: 1, 79-81, 2015